LOGO REDESIGN FOR BUNNYSUNNY.CO: A STRATEGY TO STRENGTHEN BRAND IDENTITY IN KNITTED CRAFTS - Natasya Putri, Elisabet; Prameswari, Nadia Sigi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Bunnysunny.co is a small and medium-sized enterprise (SME) specializing in handmade knitted crafts with a feminine, cheerful, loving, and warm aesthetic. However, its previous visual identity was found to be inconsistent in conveying these brand values, leading to the need for a logo redesign to enhance its brand image. This study aimed to redesign the visual identity of Bunnysunny.co to make it more relevant, communicative, and visually aligned with the brand's character. The methods used included a SWOT analysis of the existing logo and the distribution of a questionnaire to 33 respondents to compare perceptions of the old and new logos. The analysis identified areas for improvement, while the questionnaire results showed that the majority of respondents viewed the new logo as more attractive, professional, and better representative of the product's character. Despite a few minor suggestions for refinement, the redesigned logo was generally well-received and considered successful in strengthening the product image. The design process explored the use of a rabbit symbol to reflect the brand’s smart, responsive, and adaptable identity, combined with a color palette of pink, yellow, and white to evoke a cheerful, warm, and handmade feel. The final result was a comprehensive and practical visual identity system intended to increase the brand’s competitiveness and foster a more positive consumer perception.